Novel Tacrine‐Grafted Ugi Adducts as Multipotent Anti‐Alzheimer Drugs: A Synthetic Renewal in Tacrine–Ferulic Acid Hybrids. Issue 3 (23rd December 2014) - Benchekroun, Mohamed; Bartolini, Manuela; Egea, Javier; Romero, Alejandro; Soriano, Elena; Pudlo, Marc; Luzet, Vincent; Andrisano, Vincenza; Jimeno, María‐Luisa; López, Manuela G.; Wehle, Sarah; Gharbi, Tijani; et al.
Abstract Herein we describe the design, multicomponent synthesis, and biological, molecular modeling and ADMET studies, as well as in vitro PAMPA‐blood–brain barrier (BBB) analysis of new tacrine–ferulic acid hybrids (TFAHs). We identified (E)‐3‐(hydroxy‐3‐methoxyphenyl)‐N‐8[(7‐methoxy‐1, 2, 3, 4‐tetrahydroacridin‐9‐yl)amino]octyl‐N‐[2‐(naphthalen‐2‐ylamino)2‐oxoethyl]acrylamide (TFAH 10 n) as a particularly interesting multipotent compound that shows moderate and completely selective inhibition of human butyrylcholinesterase (IC50=68.2 nM), strong antioxidant activity (4.29 equiv trolox in an oxygen radical absorbance capacity (ORAC) assay), and good β‐amyloid (Aβ) anti‐aggregation properties (65.6 % at 1:1 ratio); moreover, it is able to permeate central nervous system (CNS) tissues, as determined by PAMPA‐BBB assay. Notably, even when tested at very high concentrations, TFAH 10 n easily surpasses the other TFAHs in hepatotoxicity profiling (59.4 % cell viability at 1000 μM), affording good neuroprotection against toxic insults such as Aβ1–40, Aβ1–42, H2O2, and oligomycin A/rotenone on SH‐SY5Y cells, at 1 μM. The results reported herein support the development of new multipotent TFAH derivatives as potential drugs for the treatment of Alzheimer′s disease.